Experimental results of H-mode power threshold with lower hybrid wave heating on the EAST tokamak. (3rd June 2016) - Huang, Canbin; Gao, Xiang; Liu, Zixi; Han, Xiang; Zhang, Tao; Wang, Yumin; Zang, Shoubiao; Kong, Defeng
Abstract: The density roll-over dependence on H-mode power threshold is observed on EAST for the first time. In campaign 2014 and 2015 shots with a toroidal field of 2.25 T have observed roll-over dependence with lower hybrid wave as the only auxiliary heating method, while shots with a toroidal field of 1.79 T and 1.9 T exhibit linear dependence consistent with scaling law. The density of minimum power for accessing H-mode on EAST has different plasma current values of 400 kA and 500 kA, and is better described in the normalized Greenwald fraction n ^ e, min / n G   ≈   0.4 at B T = 2.35   T . The absence of n ^ e, min in 1.7 T and 1.8 T may be attributed to the positive dependence with toroidal field. Besides, correlation analysis of H-mode power threshold and divertor geometry in scanning X -point is summarized and compared. Outer leg length (distance from X -point to outer strike point) has the highest correlation coefficient with H-mode power threshold, which explains the data scattering within the same plasma parameters. A new equation of scaling law is proposed: P th_EAST = 4.27 OLL 1.4 × P th_08 .   Neutral particles are believed to be the hidden factor in different divertor geometry, and play a negative role in L–H transition via charge exchange damping.